PENGARUH BERKUMUR DENGAN LARUTAN MADU TERHADAP pH SALIVA PADA MAHASISWA JURUSAN KEPERAWATAN GIGI BUKITTINGGI - Anses Warman; Arnetty Arnetty; Nova Herawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Saliva is biological layer that covers the entire surface of the tissues in oral cavity, the functionof saliva is to keep balance the oral cavity especially for the cause decaying teeth. Honey is important in health science specially in dental and mouth health. High mineral in honey can balancing the pH which potentially become alkali. The purpose of this research is to know the effect of gargling by honey liquid towards students saliva ofdental nursing department of Bukittinggi.This is experiment research, the number of sampel 50 participant from students dental nursing department in third semester. This research use random sampling technique. The data were obtained by observing and direct checking towards students dental nursing department. Result of this study showed that from 50 students in third semester sample 26 students ( 52 % ) have pH alkali saliva, 12 sample ( 24 % ) have pH acid and neutral. From the data above, the research did “ paired test ” and probably score 0.000 it mean it lower 0,05 ( p < 0,005 ). Conclusion of this study show there is effect of gargling by honey with pH saliva, so the people is recommended to consume honey to keep teeth and mouth